Ensino agrícola e extensão rural no Espírito Santo: a escola prática de agricultura de Santa Teresa (1940- 1948) - Santos, Marcelo Monteiro dos (2023)
The research on screen aims to analyze the process of creation and development of the Escola Prática de Agricultura in the municipality of Santa Teresa, Espírito Santo, between 1940 and 1948. The theoretical methodological approach was anchored in Italian micro-history (GINZBURG, 1989) when seeking the relationships between the microcosm of that educational institution in its relationship with the regional and national macrocosm in a period extended to the entire first half of the 20th century. The sources deposited in the Memory Center of the Santa Teresa campus were taken as a privileged documentary corpus, such as reports, periodicals, photographs, registration books, correspondence, and letters. The questions that guided the proposed objective were: a) understanding the trajectory of agricultural education in Espírito Santo in the first half of the 20th century; b) analyze the process of implementation and consolidation of the Escola Prática de Agricultura and its consolidation occurred between 1940 and 1948; c) analyze the organization of the institution’s curricular practices, considering the activities and events produced and promoted in the relationship between teaching and rural extension, as well as between the school and the local community. The work demonstrated that the Escola Prática de Agricultura, in contrast to other agricultural teaching experiences in Espírito Santo, had a trajectory of stability and growth in the 1940s, becoming a technical education institution with strong penetration in the state's rural community. based on the interrelationship between teaching and rural extension.